“DAVID PSALMS” BY TARAS SHEVCHENKO AND LINA KOSTENKO IN THE ASPECT OF INTERTEXTUALITY - Cherednуk , L. A. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2019)
The article discusses intertextuality as a specific feature of fiction of the XIX-XXI centuries, is a peculiar communication code of the author with the reader, helps him to understand not only himself, but also the world in which he lives. Intertext appears in works of literature in the form of citations, allusions, reminiscences, parodies and imitations of other people's stylistic properties. Scientific intelligence analyzes the features of the structure of the Book of Psalms, which is one of the books of the Old Testament of the Bible, addresses the problem of authorship of a monument to world culture. The article analyzes separate poems from the cycle David of Psalms, which both artists have. Of course, each of the poets can trace the interpretation of the biblical text of an outstanding literary and cultural attraction. In the process of analysis, it was found that T. Shevchenko’s works are characterized by deep connections with ancient culture, Slavic mythology, and many European literatures. The “David Psalms” cycle of modern Ukrainian poetess Lina Kostenko is full of modern realities, acute social conflicts, which is a feature of the poetess’s creative manner. It is defined as the original features of the biblical text copying by each writer, and the presence of common features. It is established that in the works of both poets, despite the difference in time, metaphysical ideas take place, reflecting universal moral and ethical principles, opposing the concepts of “good – evil”, “truth – untruth”, “glory – hula”, are widely used Church Slavonic dictionary, there are elements of introspection. The works of Taras Shevchenko and Lina Kostenko are full of deep feelings about contemporary being, creating a unique image of a literary hero, which is a reflection of the author's position. Entering into the main text the motives of intertextuality allows you to create a unique idiostyle of both artists at different levels of literary reception.